Inborn Errors of Immunity in the Premature Infant: Challenges in Recognition and Diagnosis - Gordon, Scott M.; O’Connell, Amy E. (Frontiers in Immunology, 2021)
Due to heightened awareness and advanced genetic tools, inborn errors of immunity (IEI) are increasingly recognized in children. However, diagnosing of IEI in premature infants is challenging and, subsequently, reports of IEI in premature infants remain rare. This review focuses on how common disorders of prematurity, such as sepsis, necrotizing enterocolitis, and bronchopulmonary dysplasia, can clinically overlap with presenting signs of IEI. We present four recent cases from a single neonatal intensive care unit that highlight diagnostic dilemmas facing neonatologists and clinical immunologists when considering IEI in preterm infants. Finally, we present a conceptual framework for when to consider IEI in premature infants and a guide to initial workup of premature infants suspected of having IEI.